An Analysis the Character Education in Student’s Textbook Entitled English Skills for the Future for 10th Grade Publishing by Grafindo Media Pratama - Sucita Mova Lestari; Feny Martina; Irwan Satria (International Journal of Innovation and Education Research, 2023)
Character education is everything that is the teacher, who is capable of influencing the character of the learner. The teacher helps shape the disposition of learners. It's exemplary how a teacher behaves, how a teacher talks or conveys material, how teachers tolerate, and various other related things. The aim of this research is to found the character education in the English Textbook of 2013 curriculum entitled “English for the Future for Grade X of Senior High School Students published by Grafindo Media Pratama”. This researcher use the methodology Qualitative content analysis in this research. Qualitative content analysis goes beyond counting words or extracting objective content from texts to examine meanings, themes and patterns that may be manifest or latent in a particular text. The result showed that character education found in the English textbook of 2013 curriculum entitled English for the Future for tenth grade of Senior High school Students Published by Grafindo Media Pratama. The researcher found there is 18 character education in this book, those, religious approximately 7.3% found the this book, honest around 3.3%, tolerance about 0.6%, discipline approximately 12.1% , hardwork 12.67%, creative 13,3%, independent 0.6%, democratic 4.67%, curiosity 12%, nationalism 4%, patriotism 2.67%, rewarding achievement 2.67%, friendly/communicate 6%, love of peace 0.67%, love to read 6.67%, caring the environment 2%, social care 6.67%, and responsibility 9.33%. The second question is about how the character education were delivery in this book. The researcher found there is 82.14% character education were deliver implicitly in this book, while the character education the deliver explicitly is about 17.86%.